FORMATION OF PODIFORM DUNITES IN THE LYCIAN PERIDOTITE NAPPES (AĞLA - KOYCEĞIZ, SW TURKEY) - Akbulut, Mehmet; Çolak, Mümtaz; Oyman, Tolga; Gnos, Edwin; Pişkin, Özkan (Ofioliti, 2009)
In this study, the whole-rock major oxides, trace elements and mineral chemistry of the A¿la peridotites (comprising host harzburgites and podiform dunites) are investigated to determine the formation mechanisms of the A¿la podiform dunites (SW Turkey). The whole-rock Al2O3, CaO, and MgO contents (wt %) of the all A¿la peridotites indicate a marked depletion in these elements. Al2O3 (wt%) of ortho- and clino-pyroxenes, Cr# of spinels and the Fo component of olivines from A¿la peridotites support this trend with much higher degrees of depletion in the podiform dunites. The existence of reaction/replacement textures accompanying the primary mantle texture in the low to moderately depleted harzburgite host rock suggests reaction with a melt post-dating the firststage partial melting that took place in a mid-ocean ridge setting. The boninitic affinity of the A¿la podiform dunites suggests that they are products of a Mgrich melt influx into the already depleted harzburgite host. This kind of melt may be produced by partial melting of a depleted peridotite source caused by H2O-rich fluids liberated from a subducted slab beneath a subduction zone. The low equilibration temperatures and higher Dlog (fO2) FMQ of A¿la harzburgites and podiform dunites support this consideration and indicate that this melt/rock interaction process occurred in a supra-subduction zone.